2017
DOI: 10.5530/jppcm.2017.2.17
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing and Utilization Trends of Anti-Asthmatic Drugs amongst Children in a Tertiary Care Hospital in Lahore, Pakistan

Abstract: Objective: To describe and analyze the prevalent prescribing trends of anti-asthmatics drugs among 1-12 year old children in Lahore, a major city of Pakistan, is the objective of this study.In addition, the study attempts to determine the most prevalent type of asthma amongst the stated age group of subjects. Method: Drug utilization data was recorded from 100 prescriptions collected from Children Hospital, Model Town, Lahore, during the study period of December 2014 to December 2015. The study subjects were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
3
7
0
Order By: Relevance
“…In this study also, asthma was reported to be more prevalent in males (50.67%). These findings are similar to studies by Garje, et al 17 and Shah, et al 18 and Ahmed, et al 19 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study also, asthma was reported to be more prevalent in males (50.67%). These findings are similar to studies by Garje, et al 17 and Shah, et al 18 and Ahmed, et al 19 .…”
Section: Discussionsupporting
confidence: 92%
“…Majority of the children were suffering from intermittent asthma and this finding is consistent with a study conducted by Ahmed, et al 19 . On the other hand, in a study by Garje, et al 17 , majority of patients had mild persistent asthma.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This difference may be due to, majority of children were taking controller therapy. A study conducted by Ali Ahmed et al in Lahore showed intermittent asthma, the most frequent severity and there was no child with severe persistent asthma 14 , this difference may be due controller therapy taken by children.…”
Section: Figure-1 Frequency Of Severity Of Asthma In Children N=106mentioning
confidence: 96%
“…[1] This hypersensitivity is triggered by the allergen exposures, air pollution, cigarette smoking and noxious particle insult.…”
Section: Introductionmentioning
confidence: 99%